Effect of Eye Pigmentation on Transscleral Drug Delivery - Cheruvu, Narayan P. S. (2008)
PURPOSE: To determine the influence of eye pigmentation on transscleral retinal delivery of celecoxib. METHODS: Melanin content in ocular tissues of both the strains was determined by sodium hydroxide solubilization method. The affinity of celecoxib to synthetic and natural melanin was estimated by co-incubating celecoxib and melanin in isotonic phosphate-buffered saline. The binding affinity (k) and the maximum binding (r(max)) for celecoxib to both natural and synthetic melanin were estimated. Suspension of celecoxib (3 mg/rat) was injected periocularly into one eye of Sprague-Dawley (SD, albino) and Brown Norway (BN, pigmented) rats. The animals were euthanatized at the end of 0.25, 0.5, 1, 2, 3, 4, 8, or 12 hours after the drug was administered, and celecoxib levels in ocular tissues (sclera, choroid-RPE, retina, vitreous, lens, and cornea) were estimated with an HPLC assay. In addition, celecoxib-poly(lactide) microparticles (750 μg drug/rat) were administered periocularly in SD and BN rats, and celecoxib levels in these eye tissues were assessed on day 8, to determine the effectiveness of the sustained release system. RESULTS: The r(max) and k for celecoxib’s binding to natural melanin were (3.92 ± 0.06) × 10(−7) moles/mg of melanin and (0.08 ± 0.01) × 10(6) M(−1), respectively. The affinity and the extent of celecoxib’s binding to natural melanin were not significantly different from those observed with synthetic melanin. The concentrations of melanin in choroid-RPE, sclera, and retina of BN rats were 200 ± 30, 12 ± 4, and 3 ± 0.2 μg/mg tissue, respectively. Melanin was not detectable in the vitreous, lens, and cornea of BN rats. In SD rats, melanin was not detected in all tissues assessed except in the choroid-RPE, wherein melanin-like activity was 100-fold less than in BN rats. The area under the curve (AUC) for tissue concentration versus time profiles for animals administered with celecoxib suspension was not significantly different between the two strains for sclera, cornea, and lens. However, the retinal (P = 0.001) and vitreal (P = 0.001) AUCs of celecoxib in the treated eyes were approximately 1.5-fold higher in SD rats than in BN rats. Further, the choroid-RPE AUC in the treated and untreated eyes, respectively, were 1.5-fold (P = 0.001) and 2-fold (P = 0.0001) higher in BN rats than in SD rats. With celecoxib-poly(lactide) microparticles, choroid-RPE, retina, and vitreous concentrations on day 8 exhibited similar trends in differences between the two strains, with the differences being greater than those recorded for the celecoxib suspension. CONCLUSIONS: Transscleral retinal and vitreal drug delivery of lipophilic celecoxib is significantly lower in pigmented rats than in albino rats. This difference may be attributable to significant binding of celecoxib to melanin and its accumulation/retention in the melanin-rich choroid-RPE of pigmented rats. The hindrance of retinal and vitreal drug delivery by the choroid-RPE in pigmented rats is also true of sustained-release microparticle systems.